2015
DOI: 10.1074/jbc.m115.676734
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Function Studies of Maternal Milk-derived MicroRNAs

Abstract: Background: It is unclear whether maternal milk microRNAs are taken up by offspring.Results: Milk microRNAs are not taken up into murine offspring tissues or blood but are degraded by the digestive system.Conclusion: It is unlikely that milk microRNAs function through canonical microRNA silencing.Significance: Nutritionally derived microRNAs are unlikely to cross the intestinal barrier and influence gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 41 publications
4
118
0
1
Order By: Relevance
“…99,100 Transgenic mouse studies found no uptake of specific milk microRNAs. 101,102 Finally, positive results from a milk intake study involving humans 103 could not be validated. 104 Exciting and new concepts in the microRNA oeuvre must be supported by rigorous data.…”
Section: Case Studies To Identify Rigor and Reproducibility Challengementioning
confidence: 99%
“…99,100 Transgenic mouse studies found no uptake of specific milk microRNAs. 101,102 Finally, positive results from a milk intake study involving humans 103 could not be validated. 104 Exciting and new concepts in the microRNA oeuvre must be supported by rigorous data.…”
Section: Case Studies To Identify Rigor and Reproducibility Challengementioning
confidence: 99%
“…It has been suggested that miRNAs can be transferred from breast milk to the bloodstream (Munch et al 2013;Baier et al 2014;Izumi et al 2015), although these results have also been contested (Laubier et al 2015;Title et al 2015).…”
Section: Controlled Feeding In Piglets Does Not Support Transfer Of Mmentioning
confidence: 99%
“…42 In the other 2 models, miR-375 and miR-200c/141 knockout mice fed by wild-type wet nurse mice were explored. 42,45 Only a modest increment in the plasma concentration of these 2 miRNAs was noted, and the authors concluded that milk miRNAs serve just as a dietetic source. However, both miR-375 and miR-200c might also affect exosome formation via exocytotic/endocytotic pathways, 42,48,49 and the required amount of miRNAs for biological activity is also intensively debated.…”
Section: Dietary Milk-derived Mirnasmentioning
confidence: 99%